2002
DOI: 10.4049/jimmunol.169.8.4379
|View full text |Cite
|
Sign up to set email alerts
|

Uniquely Conformed Peptide-Containing β2-Microglobulin- Free Heavy Chains of HLA-B2705 on the Cell Surface

Abstract: The human class I MHC molecules are known to generally exist on the cell surface either as peptide-containing complexes of H chain (α-chain) and β2-microglobulin (β2m) or as β2m-free H chains incapable of binding peptides. In this study, a uniquely conformed peptide-containing β2m-free HLA-B2705 H chain has been isolated using the recently described highly efficient perfusion-affinity chromatography system for purification of class I MHC protein molecules. This form recognized by the mAb MARB4 is very closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
(42 reference statements)
2
27
0
Order By: Relevance
“…Instead, they appear to derive from cell surface H chain/␤ 2 m/peptide complexes that have lost ␤ 2 m (19). Consistent with this observation, relatively stable ␤ 2 m-free HLA-B27 H chains have been found on the cell surface (21). Thus, cell surface dimer formation appears to be mechanistically distinct from HLA-B27 misfolding.…”
supporting
confidence: 69%
“…Instead, they appear to derive from cell surface H chain/␤ 2 m/peptide complexes that have lost ␤ 2 m (19). Consistent with this observation, relatively stable ␤ 2 m-free HLA-B27 H chains have been found on the cell surface (21). Thus, cell surface dimer formation appears to be mechanistically distinct from HLA-B27 misfolding.…”
supporting
confidence: 69%
“…However, these studies did not look for evidence of homodimerization. Very recently, Malik et al [35] described a population of peptide-containing g 2 m-free HLA-B27 monomers on the surface of transfected lymphoblastoid cell lines that react with the mAb MARB4. The MARB4-reactive species are distinct from the HC-10-reactive molecules and are contained within the ME-1-reactive cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, have demonstrated multiple HC-dimeric structures, which may form independently in the ER during the early stages of biosynthesis or at the cell surface following unfolding of normal HLA-B27 molecules, possibly involving trafficking through an endocytic compartment. The existence of HC-dimers has been called into question (48). In our own experience, we find that some HCdimers may be formed as a result of inefficient sample alkyla- tion, especially those deriving from the cell surface.…”
Section: Effect Of Reduced Temperature and Cysmentioning
confidence: 93%